Accumulation patterns of lipophilic organic contaminants in surface sediments and in economic important mussel and fish species from Jakarta Bay, Indonesia. Issue 2 (30th September 2016) - Dwiyitno,; Dsikowitzky, Larissa; Nordhaus, Inga; Andarwulan, Nuri; Irianto, Hari Eko; Lioe, Hanifah Nuryani; Ariyani, Farida; Kleinertz, Sonja; Schwarzbauer, Jan
Abstract: Non-target screening analyses were conducted in order to identify a wide range of organic contaminants in sediment and animal tissue samples from Jakarta Bay. High concentrations of di- iso -propylnaphthalenes (DIPNs), linear alkylbenzenes (LABs) and polycyclic aromatic hydrocarbons (PAHs) were detected in all samples, whereas phenylmethoxynaphthalene (PMN), DDT and DDT metabolites (DDX) were detected at lower concentrations. In order to evaluate the uptake and accumulation by economic important mussel ( Perna viridis ) and fish species, contaminant patterns of DIPNs, LABs and PAHs in different compartments were compared. Different patterns of these contaminant groups were found in sediment and animal tissue samples, suggesting compound-specific accumulation and metabolism processes. Significantly higher concentrations of these three contaminant groups in mussel tissue as compared to fish tissue from Jakarta Bay were found. Because P. viridis is an important aquaculture species in Asia, this result is relevant for food safety. Highlights: Analyses of surface sediment and animal tissue samples from a tropical coastal system Non-target screening enabled identification of a wide range of organic contaminants. Comparison of contaminant patterns in surface sediments and animal tissue samples Results illustrate compound-specific accumulation and metabolism processes. Higher concentrations of all contaminants in mussel tissue as compared to fish tissue